Low uptake of hepatitis B vaccination among healthcare workers in primary health facilities in Mwanza region, North-Western Tanzania - Ndunguru, Bernada; Wilfred, Diana; Kapesa, Anthony; Kilonzo, Semvua D.; Mirambo, Mariam; Hyera, Fred; Massaga, Fabian (Frontiers in Public Health, 2023)
Abstract Background: Despite the availability of hepatitis B vaccines (HBV) in Tanzania, its uptake among healthcare workers (HCWs) in high levels facilities like the tertiary hospitals where the vaccines are available is low. However, its uptake among HCWs in primary health facilities remains understudied. Lack of this information limits scaling up of HBV vaccination programs. Methodology: A cross-sectional analytical study was conducted between June and July 2022 among HCWs in Misungwi and Ilemela districts that were selected purposively. The sample size was calculated using the Taro Yamane formula, and data were collected using a self-administered questionnaire and analyzed using IBM SPSS® version 25. Results: A total of 402 HCWs were recruited, their mean age was 34.9±7.77 years, only (18% (76/402) reported being fully vaccinated.HCWs in Ilemela showed higher uptake (χ2=23.64, df=1, p=0.00) of the vaccine as compared to HCWs in Misungwi. Being male (aOR=2.38, 95% CI 1.28-4.45, p=0.006), working in an urban setting (aOR=5.75, 95% CI 2.91-11.35, p=0.00), employment duration of more than two years (aOR=3.58, 95%CI 1.19-10.74, p=0.023) were significantly associated with higher odds of vaccination. Moreover, high perceived susceptibility to HBV infection (aOR=2.20, 95% CI1.02-4.75, p=0.044) and history of needle prick injuries (aOR=6.87, 95%CI 3.55-13.26, p=0.00) were significantly associated with higher odds of HBV vaccination. Conclusion: Low uptake of HBV vaccine among HCWs in primary health facilities was observed with a noteworthy difference between rural and urban settings. Therefore, advocacy campaigns as well as resource mobilization towards the promotion of HBV vaccination in primary health facilities are pivotal.